1994
DOI: 10.1128/aac.38.7.1588
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities to clarithromycin and erythromycin of isolates of Chlamydia pneumoniae from children with pneumonia

Abstract: We tested in vitro 49 isolates of Chlamydia pneumoniae obtained from 35 children with community-acquired pneumonia against clarithromycin and erythromycin. The children were part of a treatment study comparing the two drugs. Clarithromycin was 2-to 10-fold more active than erythromycin, with a MIC for 90%6 of strains tested and minimal chlamydiacidal concentration for 90%Yo of strains tested of 0.031 ,ig/ml compared with 0.125 ,ug/ml for erythromycin. Eight of these children, two of whom were treated with eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 7 publications
(4 reference statements)
2
25
0
Order By: Relevance
“…All these children improved clinically despite persistence of the organism. Persistence did not appear to be related to the development of antibiotic resistance since all the isolates remained susceptible to erythromycin and clarithromycin during and after treatment (119). The experience with azithromycin has been similar.…”
Section: Treatment Of C Pneumoniae Infection: Backgroundmentioning
confidence: 65%
See 1 more Smart Citation
“…All these children improved clinically despite persistence of the organism. Persistence did not appear to be related to the development of antibiotic resistance since all the isolates remained susceptible to erythromycin and clarithromycin during and after treatment (119). The experience with azithromycin has been similar.…”
Section: Treatment Of C Pneumoniae Infection: Backgroundmentioning
confidence: 65%
“…pneumoniae is susceptible in vitro to a wide range of antimicrobial agents, including macrolides, tetracyclines, and quinolones, that target either protein or DNA synthesis (Table 6) (39,52,53,54,119,120,121). Recently, Gieffers et al (39) reported that the in vitro susceptibilities of five isolates of C. pneumoniae cultured from vascular tissue did not differ significantly from those of respiratory isolates.…”
Section: Treatment Of C Pneumoniae Infection: Backgroundmentioning
confidence: 99%
“…All of these children improved clinically despite persistence of the organism. Persistence was not related to the development of antibiotic resistance as all isolates remained susceptible to erythromycin and clarithromycin during and after treatment [51]. Clarithromycin is 10±100-fold more active than erythromycin in vitro and has superior pharmacokinetics and tissue penetration, and yet was not more effective than erythromycin in eradicating C. pneumoniae from the respiratory tract.…”
Section: Treatmentmentioning
confidence: 91%
“…The standard treatment with steroids and bronchodilators was equivalent in clarithromycin-treated and nonantibiotictreated children as regards the drugs used and the length of therapy. Clarithromycin was chosen based on the in vitro susceptibility to macrolides of M. pneumoniae and C. pneumoniae [13,14]. The duration of therapy was based on previous clinical observations from use of this antibiotic in children [15,16].…”
Section: Study Subjectsmentioning
confidence: 99%